Seroprevalence of antibodies against Kaposi's sarcoma-associated herpesvirus among HIV-negative people in China - Zhang, Tiejun (Infect Agent Cancer, 2017)
BACKGROUND: Little information on the prevalence of Kaposi’s sarcoma associated herpesvirus (KSHV) among HIV-negative individuals is available from Asia. METHODS: In the present study, we report findings from a new survey of KSHV in 983 HIV-negative male migrants from Shanghai and their combination with previous similar surveys of 600 female migrants, 600 female sex-workers (FSW), 1336 sexually transmitted infection (STI) clinic male patients, 439 intravenous drug-users (IVDU), and 226 men having sex with men (MSM) from China. KSHV-specific antibodies against latent and lytic antigens were assessed using Sf9 and BC3 monoclonal immunofluorescence assay. Age-adjusted prevalence ratios (PR) and 95% confidence interval (95% CI) for KSHV-positivity were estimated using Poisson regression. RESULTS: In total, 4184 HIV-negative participants were included. KSHV prevalence ranged from 9.8% (95% CI: 7.9%-11.7%) in male migrants to 32.3% (95% CI: 24.1%-34.1%) in MSM. IVDU show intermediate level (17.5%, 95%CI: 14.1%-21.4%). KSHV was associated with syphilis (PR = 2.03, 95% CI: 1.38-2.98) in MSM but not in other groups. An association with human herpes virus 2 was also found among MSM (PR = 1. 83, 95%: 1.22-2.75) but not in migrant workers or FSW. CONCLUSIONS: KSHV prevalence in HIV-negative heterosexuals, FSW, and STI male patients from China is approximately 10%, but 2- and 3-fold higher in IVDU and MSM, respectively. Associations of KSHV with STIs among MSM only suggest that sexual transmission of the virus is important in MSM but not in heterosexuals.